Determination of predictive factors for the clinical cure rate of endometritis in Holstein dairy cows - Hajibemani, A; Mirzaei, A (Journal of the Hellenic Veterinary Medical Society, 2023)
Endometritis is one of the most common disorders that negatively influence reproductive performance in dairy cows. The purpose of this study was to determine the predictive factors of the clinical cure of endometritis. A total of 700 Holstein dairy cows were examined for signs of clinical endometritis between 30 and 40 days in milk (the first examination in the time of clean test). A total of 131 cows with clinical endometritis were assigned for treatment. Cytological examination, reagent test strips, and characteristics of reproductive organs were evaluated at the time of treatment (the first examination) and two weeks after the treatment (the second examination: for evaluation of response to treatment of endometritis). After evaluation of treatment, cows were grouped into the responsive (n=56) and unresponsive (n=75) to treatment. Percentages of non-degenerated neutrophil (NDN), degenerated neutrophil (DN), total neutrophils and leukocyte esterase activity were significantly higher (P<0.05) in the unresponsive cows than those of responsive ones to treatment at the second examinations. Moreover, the nitrate test was significantly higher in the unresponsive group than the responsive group at the first examination. However, protein concentration and percentages of lymphocyte cells were significantly higher in the unresponsive animals than the responsive cows at the first and second stages of examination (P<0.05). Increasing of lymphocytes percentage, protein concentration, and nitrate test at the first stage of examination in the unresponsive cows showed more sever of inflammatory conditions and uterine infection in the unresponsive cows. Evaluation of these factors can predict the clinical cure of endometritis in dairy cows.